Comparison of Stifle Biomechanics after Two Different Techniques of Cranial Cruciate Ligament Repair - Davidson, Jacqueline R.; Bauer, M.S.; Aiken, S.W.; Toombs, J.P.; Prostredny, J.M. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Stifle joint biomechanics were evaluated by analysis of instant centre of motion, after cranial cruciate ligament transection and after stifle joint stabilization, using either the fibular head transposition or the under-and-over fascial strip technique. The instant centres of motion and resulting velocity vectors were determined by radiographic evaluation of the stifle of twelve fresh cadavers before and after cranial cruciate ligament transection, and after stabilization of the stifle joint by either the fibular head transposition or the under-and-over fascial strip technique. All 12 stifles had normal instant centres of motion before transection of the cranial cruciate ligament, and 10 of 12 were normal after transection. All six stifles repaired by fibular head transposition retained normal instant centre of motion. Abnormal instant centres of motion were present in three of six stifles repaired by the under-and-over technique. These differences were not statistically significant.Stifle joint biomechanics were evaluated by analysis of instant centre of motion after cranial cruciate ligament transection and after stifle joint stabilization using either the fibular head transposition or the underand-over fascial strip technique. Neither surgical technique consistently resulted in abnormal instant centres of motion.
Keywords: Cruciate ligament; instant centre of motion; fibular head transposition; under-and-over fascial strip